Evaluasi Kenyamanan Jalur Pejalan Kaki Bagi Mahasiswa Pada Kawasan Universitas Syiah Kuala - Amira Fudla; Zya Dyena Meutia; Reza Maulana Haridhi (Prodi Arsitektur, Fakultas Sains dan Teknologi bekerja sama dengan Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Islam Negeri Ar-Raniry Banda Aceh, 2024)
Syiah Kuala University is the oldest state university in Aceh located in the capital city of Aceh Province with its main campus located in the student city of Kopelma Darussalam, Banda Aceh. A pedestrian path is a movement of people from one place to another.Evaluation of the comfort of the pedestrian path in the Syiah Kuala University area is based on the existence of several pedestrian areas that have been damaged, potholed and misused.